A closer look at IIsaac Oluwole Delano’s A Dictionary of Yoruba Monosyllabic Verbs - Toyin Falola; Michael Oladejo Afolayan (Yoruba Studies Review, 2021)
What follows is a revised version of our introductory segment to Isaac O. Delano’s A Dictionary of Yoruba Monosyllabic Verbs. In it, we provided a historical narrative of the emergence of the dictionary as the main tool for lexicographers. We also attempted to construct the historical assumptions of what could be construed as the value of a dictionary. We spoke to the utility of the dictionary and lamented over its obvious underutilization. We then went ahead to provide the various types of dictionaries and their value as a modern research tool. With the introduction, and having established the significance of a dictionary, we looked specifically at Delano’s pioneering work of the monosyllabic dictionary specifically.